Comparison of Unilateral Biportal Endoscopy Decompression and Microscopic Decompression Effectiveness in Lumbar Spinal Stenosis Treatment: A Systematic Review and Meta-analysis - Li Junjie; Yin Jiheng; Liu Jun; Lin haixiong; Yuan Haifeng (Asian Spine Journal, 2023)
This study aimed to compare the safety and effectiveness between unilateral biportal endoscopy (UBE) technique and microscopic decompression (MD) technique in lumbar spinal stenosis treatment. PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure, and other databases were used to conduct extensive literature searches. RevMan ver. 5.3 software was used for the statistical analysis. Eleven studies were included with 930 patients, including 449 patients in the UBE group and 521 in the MD group. Both techniques revealed similar operative times at −1.77 minutes (95% confidence interval [CI], −7.59 to 4.05 minutes; p=0.55), the postoperative dural expansion area at −1.27 (95% CI, −19.30 to 16.77; p=0.89), the postoperative complications at 0.76 (95% CI, 0.47 to 1.22; p=0.26), the preoperative Visual Analog Scale (VAS) for leg pain, and the last follow-up (>12 months) VAS for leg pain at −0.04 (95% CI, −0.14 to 0.06; p=0.47), the preoperative Oswestry Disability Index (ODI), and the last follow-up (>12 months) ODI scores at −0.18 (95% CI, −0.76 to 0.40; p=0.54), and patient satisfaction (the modified MacNab score) at 1.15 (95% CI, 0.54 to 2.42; p=0.72). However, intraoperative bleeding was lower following the UBE technique at −52.78 mL (95% CI, −93.47 to −12.08 mL; p=0.01) and was shorter following the UBE technique at −3.06 (95% CI, −3.84 to −2.28; p<0.01). UBE and MD technology have no significant differences in efficacy or safety in the treatment of patients with lumbar spinal stenosis based on this meta-analysis. However, the UBE technique has less intraoperative bleeding and a shorter hospital stay. It has a slight advantage and is a better surgical option than the MD technique. It can be an alternative minimally invasive spinal surgery method.